2003
DOI: 10.1124/dmd.31.11.1409
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition of Novel Des-Fluoro Quinolone Garenoxacin in Experimental Animals and an Interspecies Scaling of Pharmacokinetic Parameters

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Garenoxacin is a novel quinolone that does not have a fluorine substituent at the C-6 position in the quinoline ring. Garenoxacin or 14 C-garenoxacin was intravenously or orally administered to rats, dogs, and monkeys. Metabolic profiles and pharmacokinetic parameters were investigated focusing on the species differences and the allometric scaling of pharmacokinetic parameters. Garenoxacin was well absorbed following oral administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…It was reported that N-carbamoylation proceeded through a stable carbamic acid interme- diate that could be isolated from plasma. Such other stable carbamic acid was reported by Hayakawa et al (2003) for garenoxacin in rat and monkey bile and in dog feces and for metoclopramide in our laboratory .…”
Section: Carbamoyl Glucuronidesmentioning
confidence: 79%
See 1 more Smart Citation
“…It was reported that N-carbamoylation proceeded through a stable carbamic acid interme- diate that could be isolated from plasma. Such other stable carbamic acid was reported by Hayakawa et al (2003) for garenoxacin in rat and monkey bile and in dog feces and for metoclopramide in our laboratory .…”
Section: Carbamoyl Glucuronidesmentioning
confidence: 79%
“…N-Carbamoyl glucuronide conjugate of varenicline was identified in plasma and urine of rat, monkey, and human, but not mouse (Obach et al, 2006). Garenoxacin-N-carbamoyl glucuronide was detected in multiple species: rat and monkey bile and dog urine and feces (Hayakawa et al, 2003). Tocainide-N-carbamoyl glucuronide has been reported to be present in urine of guinea pig, dog, cat, and rabbit (Gipple et al, 1982).…”
Section: Carbamoyl Glucuronidesmentioning
confidence: 95%
“…Carbamic acid derivatives of piperazine (Kirsch et al, 2000) and des-methyl org1377 (Delbressine et al, 1990) were identified in this manner, generated after reaction of NaHCO 3 with respective parent molecules. However, stable carbamic acids have also been reported by Shaffer et al (2005) and Hayakawa et al (2003). A trans-esterification type reaction has been used as a method of trapping an unstable N-Carbamoyl glucuronides of unstable carbamic acids can convert back to parent moieties upon hydrolysis (Tremaine et al, 1989) or even during sample preparation.…”
Section: Discussionmentioning
confidence: 99%
“…This includes, RP-HPLC 2 method for assay, metabolism and deposition study in rats, monkey and dog 3 , joint cartilage study in immature rats …”
Section: Introductionmentioning
confidence: 99%